Green Tourism Concept Implementation Based On Tourist Satisfaction Level In Tapanuli Tengah Regency - Adiprayoga, Shofian Nanda; Yaqin, Husnul; Anugerah, Tirta; Nisari, Tika (International Journal of Marine Engineering Innovation and Research, 2024)
In sustainable development, Green Tourism integrates environmental preservation, community empowerment, and tourism attractions. This paper aims to develop a strategy for integrating Green Tourism into Tapanuli Tengah Regency's maritime tourism industry. This area continues to deal with a number of classic challenges, such as disorganized tourism administration, poor waste management, and a disregard for accommodations and accessibility. A comprehensive review of the regulations that were implemented in place is backed by a mixed methodology that uses the Soft System Methodology for Visitor Satisfaction Index (VSI) values and responses from different respondents. The research findings, with a satisfaction level of 80.4%, demonstrate that tourists are happy with the tourism activities. There are nonetheless, certain demands made by the guests. Planning for a more methodical and sustainable development necessitates careful consideration of current policies.The research findings outline a number of issues and their resolutions, such as the creation of first-rate amenities, instruction for operators of tourism-related businesses, the application of standard operating procedures (SOP) to ensure price parity for goods and services, and a recommendation to launch a flight route from Jakarta to Tapanuli Tengah in order to facilitate outside tourists coming to the region.